Desain Dan Analisis Varian Sudut Pisau Terhadap Uji Kinerja Mesin Pencacah Rumput - Yudi Candra, Andreas; Bagus Prasetiyo, Angger; Rudy Hartana, Dandung (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2024)
One of the nations with the most potential for the livestock industry worldwide is Indonesia. The industry of cattle farming is one among them. An animal feed processor needs a grass cutter to expedite the operation. The blade of a grass cutter is one part that significantly affects how well it operates. The purpose of this study is to evaluate lawn cutter blade performance. The census's effectiveness and success rate, as well as its results, demonstrate this. The research will conduct performance testing, such as effective capacity tests, theoretical work capacity, machine work efficiency, and yield tests, on grass chopper machines with side sharp and centre sharp blades variants. Elephant grass measuring 10 cm in diameter, 30 cm in length, and weighing 1 kg was the material used in this study. The machine used in the research had a rotational speed of 5400 rpm. The average effective working capacity of the side sharp blade was 153.83 kg/hour, and the middle sharp blade was 126.87 kg/hour, according to the results of calculations and discussions. 181.44 kg/hour is the theoretical work capacity value. The side sharp blade has an average work efficiency rating of 84%, whereas the centre sharp blade's is 70%. A side taper blade is a fantastic suggestion for a grass cutter.